Automation and Monitoring for Aquaponic System Based on NodeMcu - Ahmad Zatnika Purwalaksana; Indra Hartarto Tambunan; Andi Ray Hutauruk (Prodi Teknik Mesin, 2022)
The increase in the human population, which continues to increase accompanied by the rate of conversion of agricultural land to non-agricultural land is increasingly causing a problem of food supply. Aquaponics is one solution to this problem, but conventional aquaponics treatment must be done manually and will require a lot of time and energy in caring for it if the land is large enough. The implementation of IoT technology can help in the aquaponics treatment. This research aims to create a control and monitoring system for aquaponic cultivation built in a greenhouse. The parameter to be controlled is the water level of the fish pond using an ultrasonic hc-sr04 sensor and a solenoid valve which functions to fill the water in the pond. While the parameters to be monitored are the water level and the pH of the fish pond water. Data from the sensor is sent using the HTTP protocol by the NodeMcu microcontroller to the database via the internet network. The results of this research indicate that the control system has been successfully created where the solenoid valve will turn on when the distance between the ultrasonic sensor and the pool water level is more than 50 cm. The results of water measurements are still fluctuating due to placement of ultrasonic sensors under the water pipe to the fish pond. Meanwhile, the monitoring system will present measurement data in the form of graphs where the data will be updated every 30 minutes.